Analisis Tingkat Partisipasi Masyarakat dalam Program Pemilahan Sampah: (Studi Kasus di BTN Zam-Zam Residence, Kelurahan Watubangga, Kota Kendari Sulawesi Tenggara) - Saputra, Untung; Assiddieq , Moch.; Pratiwi, Yunita Eka (Universitas Muhammadiyah Kendari, 2026)
This study analyzes the level of community participation in the waste segregation program at BTN Zam-Zam Residence, Watubangga Village, identifies the factors influencing participation, and examines residents’ perceptions of the program’s environmental impacts. A descriptive quantitative approach was employed, with data collected through questionnaires and field observations involving 15 respondents selected using a stratified random sampling technique. Data were analyzed using descriptive statistics to assess community knowledge, attitudes, participation levels, and supporting and inhibiting factors. The results indicate that community participation in the waste segregation program falls within the good category, with an average score of 4.05. Residents demonstrated a good level of knowledge regarding waste segregation, while environmental awareness and attitudes were also categorized as positive. The main factors supporting participation include adequate knowledge, environmental awareness, and social support within the community. Conversely, participation is constrained by limited waste management facilities and insufficient public outreach and education. Community perceptions of the waste segregation program were generally favorable, reflecting recognition of its benefits in improving environmental cleanliness and supporting sustainable waste management practices. The findings suggest that the community possesses a strong foundation of knowledge and positive attitudes toward waste segregation; however, greater efforts are needed to translate these into consistent practices. Improving infrastructure and conducting continuous awareness campaigns are essential to enhancing participation rates. Therefore, active collaboration between local government and community members is necessary to ensure the long-term effectiveness and sustainability of the waste segregation program.